ON ESTIMATION OF THERMAL STRENGTHENING OF TITANIUM ALLOYS DEPENDING ON CONDITIONS AND SCHEMA OF THEIR FORGING - V. N. Fedulov (Литьë и металлургия)
The problems of thermal strengthening of forged pieces of (a + A)-titanium alloys depending on previous conditions of deformation and also on after-deformation annealing of castings are studied. The evaluation of mechanical characteristics of alloy BT23 in forged pieces of different thickness depending on location of zone by cut is given.